Gender still determines how, and how long, we work - Schmitz, Wiebke [Verfasser] (My University, 2023)
"Female-coded family work keeps women away from late working life – but it makes a difference where in Europe they live because Nordic countries do not recognize this divide.[...] Childcare impacts upon late working life – women tend to be employed part time or outside paid labor if they engaged in childcare during earlier life stages; men with children are more likely to be in full-time employment. Women are more affected by early working life decisions – previous labor-market participation or a reduction in working hours due to childcare obligations have a greater impact on late working life. A North-South divide in Europe – it is mostly in southern and western Europe that women’s domestic work or part-time employment prevents full-time employment in late working life, but in northern Europe, female employment in late working life is barely affected by previous family obligations." (excerpt; BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; 370; 300; Frauen; Frauenerwerbstätigkeit; Care work; Familienarbeit; Erwerbsverhalten; Erwerbsbeteiligung; Einflussfaktor; Geschlechterrolle; Internationaler Vergleich; Europa